Pemanfaatan Ubi Jalar Ungu Sebagai Media PertumbuhanBibit F0 Jamur Tiram dan Jamur Merang - Nurjanah, Serly; Dra. Suparti M.Si, Dra. Suparti M.Si (2016)
Purple sweet potato contains carbohydrates equivalent to carbohydrate content contained in potatoes. Purple sweet potato is also a source of vitamins and minerals include Vitamin A, Vitamin C, Vitamin B, and ribovlavin. This study aims to determine the growth of F0 seed oyster mushrooms and straw mushroom in the media on the growth of purple sweet potato mycelium. The method used was experimental research methods with completely randomized design (CRD) with two factorial is concentration purple yam and types of fungi. Data analysis technique used is the One Way ANOVA. Based on the results obtained, the average diameter of oyster mushroom mycelium growth and staw mushroom on M1J1 was 6.3 cm, M2J1 7.2 cm, 5.3 cm M3J1, M1J2 6.8 cm, 7.3 cm M2J2, M3J2 3.3 cm. So we can conclude that the purple sweet potato can be used as a growth medium F0 oyster mushrooms and staw mushroom and the best growth at concentrations of 200 grams with white mycelium and spread